If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + -3(3 + -4b) = 7 4b + (3 * -3 + -4b * -3) = 7 4b + (-9 + 12b) = 7 Reorder the terms: -9 + 4b + 12b = 7 Combine like terms: 4b + 12b = 16b -9 + 16b = 7 Solving -9 + 16b = 7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 16b = 7 + 9 Combine like terms: -9 + 9 = 0 0 + 16b = 7 + 9 16b = 7 + 9 Combine like terms: 7 + 9 = 16 16b = 16 Divide each side by '16'. b = 1 Simplifying b = 1
| 9(y-4)=5y-32 | | 5y-9+y+55=7y+50-3y | | 7a+3b=1 | | 3b+4=-7b+11 | | 7a-3b=1 | | Q=180-5p | | 9x-3+8x=2x+4-4x | | f(x)=5x^4+12x^3+-16x^2+10 | | 6.5w=-123.5 | | 9x-7x=36 | | -2x-2=50x-50 | | 6x+7x+9x=88 | | 10-3=x-9 | | R=F+460 | | 2x+y=1.25 | | 5x+2x=154 | | 6x+(-78)-30x=-6 | | 2x-8x+3x-7x= | | 15-7w=1 | | y=-1.4x+4.25 | | 3x^3+22x=0 | | 2x+8x+3x-7x= | | 2x-8x-3x-7x= | | 3(X-6)+5=8 | | 2x+8x-3x-7x= | | -b+6b=b+1+5b | | -3t+16=10 | | f(x)=5x^4+15x^2+10 | | 79+k=84 | | 9x+x=70+8x | | 7=5v-3 | | -15(x-c)=15 |